2016
DOI: 10.1038/srep19917
|View full text |Cite
|
Sign up to set email alerts
|

Combination of the Manifold Dimensionality Reduction Methods with Least Squares Support vector machines for Classifying the Species of Sorghum Seeds

Abstract: This study was carried out for rapid and noninvasive determination of the class of sorghum species by using the manifold dimensionality reduction (MDR) method and the nonlinear regression method of least squares support vector machines (LS-SVM) combing with the mid-infrared spectroscopy (MIRS) techniques. The methods of Durbin and Run test of augmented partial residual plot (APaRP) were performed to diagnose the nonlinearity of the raw spectral data. The nonlinear MDR methods of isometric feature mapping (ISOM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The PhenoGraph clustering [9] and isomap dimensionality reduction were done using R package cytofkit. [10] Hierarchical clustering was used to determine two meta-clusters based on the median of markers' expression from each PhenoGraph clusters. [11]…”
Section: Mass Cytometry (Cytof)mentioning
confidence: 99%
“…The PhenoGraph clustering [9] and isomap dimensionality reduction were done using R package cytofkit. [10] Hierarchical clustering was used to determine two meta-clusters based on the median of markers' expression from each PhenoGraph clusters. [11]…”
Section: Mass Cytometry (Cytof)mentioning
confidence: 99%
“…Feature Selection. In machine learning, one of the challenges is the selection of the best feature set from all the available feature space reported in different studies 27, [86][87][88] . The selection of entropy features extracted from interictal iEEG data could provide a more accurate classification with respect to the whole set of features.…”
Section: Tsallis Entropymentioning
confidence: 99%
“…Attaviroj et al, (2011) applied FT-NIR spectroscopy to classify five varieties of rice and achieved a high accuracy of 99.22% using the partial least-squares discriminant analysis (PLS-DA) modeling method [27]. Chen et al, (2016) showed that a reasonable accuracy can be obtained while using Fourier transform mid-infrared (FT-MIR) and FT-NIR spectroscopy to classify species of sorghum seeds [28]. Cui el at.…”
Section: Introductionmentioning
confidence: 99%